Self-Efficacy as a Protective Factor Against Academic Stress and Anxiety: Evidence from a Systematic Literature Review - Erfan Nawawi (Yayasan Al-Afif, 2025)
High academic pressure can trigger stress and anxiety among students, adversely affecting their mental health and academic performance. This study aims to examine the role of self-efficacy in reducing academic stress and anxiety, identify effective interventions, and map existing research gaps. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol, searching the ScienceDirect and Google Scholar databases using Boolean search strategies within the 2019–2024 timeframe. Of the 100 articles initially identified, 11 met the inclusion criteria and were analyzed thematically. Findings indicate that self-efficacy plays a significant protective role, both directly and through the mediation of motivation, emotional regulation, and academic engagement. Effective interventions include CBT-based stress management training, self-directed learning programs, and the enhancement of regulatory emotional self-efficacy. This study underscores the importance of self-efficacy enhancement strategies as both preventive and curative measures in educational settings while encouraging longitudinal and cross-cultural research to strengthen empirical evidence.